Bridge across the Formosa Strait: Private Law Relations between Taiwan and Mainland China - Chen, Tung-Pi (Columbia Journal of Asian Law, 1990)
Driven by forces of economic expansion and nationalist senti- ment, as well as by political and economic pragmatism, Taiwan and the People’s Republic of China (PRO) are moving toward a closer informal relationship. This paper will examine a number of legal issues arising from renewed relations between the two regions. It will first review the background to the current relationship in the political and economic contexts. In subsequent sections, the legal problems of establishing private relations in an environment of mutual public non- recognition will be discussed. Specifically, the paper will justify a legal framework for private relations, will analyze new laws and poli- cies dealing with these relations, and will examine special problems of the PRC-Taiwan relationship. Throughout this discussion, the emphasis will be on providing a theoretical and practical basis for renewed private relations.